Absceso residual post apendicetomía en la técnica quirúrgica laparoscópica versus técnica abierta en el hospital Regional de Loreto. 2022 - Vargas Barzola, Victor Emilio (2024)
GENERAL OBJECTIVE: To determine the magnitude of residual abscess after appendectomy in the laparoscopic versus open surgical technique at the Regional Hospital of Loreto 2022. MATERIALS AND METHODS: Quantitative and cross-sectional study. The study population will be all those medical records that meet the definition of laparoscopic and open appendectomy. The sample will consist of 100 medical records with convenience sampling. The hypothesis test of chi2 with the SPSS v23 statistical package will be used. CONCLUSIONS: The appendectomy technique does not seem to affect the incidence of residual abscess in uncomplicated or complicated appendicitis. However, laparoscopic appendectomy has advantages over open procedures, such as a shorter hospital stay and earlier recovery, so it should be preferred for emergency procedures.